2004
DOI: 10.5194/npg-11-35-2004
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian velocity statistics of directed launch strategies in a Gulf of Mexico model

Abstract: Abstract. The spatial dependence of Lagrangian displacement and velocity statistics is studied in the context of a data assimilating numerical model of the Gulf Mexico. In the active eddy region of the Western Gulf, a combination of Eulerian and Lagrangian measures are used to locate strongly hyperbolic regions of the flow. The statistics of the velocity field sampled by sets of drifters launched specifically in these hyperbolic regions are compared to those produced by randomly chosen launch sites. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Kantha et al (2005) used CUPOM to analyze the evolution of sixteen LCRs over a nine year period and reported that the model accurately reproduced LCR pinchoffs. CUPOM provided the mean SSH fields for the optimal interpolation of remotely-sensed SSH anomalies described by Leben (2005) and has been used to examine Lagrangian kinematics and statistics in the eastern Gulf (Kuznetsov et al, 2002;Toner and Poje, 2004). Trajectories computed using CUPOM near-surface velocities compared favorably with observed trajectories (Toner et al, 2001) and remotelysensed ocean color measurements (Toner et al, 2003) in the eastern Gulf.…”
Section: Journal Of Marine Researchmentioning
confidence: 98%
“…Kantha et al (2005) used CUPOM to analyze the evolution of sixteen LCRs over a nine year period and reported that the model accurately reproduced LCR pinchoffs. CUPOM provided the mean SSH fields for the optimal interpolation of remotely-sensed SSH anomalies described by Leben (2005) and has been used to examine Lagrangian kinematics and statistics in the eastern Gulf (Kuznetsov et al, 2002;Toner and Poje, 2004). Trajectories computed using CUPOM near-surface velocities compared favorably with observed trajectories (Toner et al, 2001) and remotelysensed ocean color measurements (Toner et al, 2003) in the eastern Gulf.…”
Section: Journal Of Marine Researchmentioning
confidence: 98%
“…In particular, the initial restriction to periodic, infinite-time systems has been overcome by focusing on transient stagnation points, finite-time analogs of stable and unstable manifolds, and analysis of finite-time data (Haller and Poje 1998;Poje and Haller 1999;Coulliette and Wiggins 2000;Miller et al 2002). These techniques have been useful in the improvement of the reconstruction of Eulerian fields from Lagrangian data (Poje et al 2002;Toner and Poje 2004) and in the performance of a Lagrangian data assimilation scheme (Molcard et al 2006). Lagrangian coherent structures (LCS) such as stable and unstable manifolds and hyperbolic trajectories help visualize the combined effect of the time variability and geometric features (such as eddies and jets) on transport.…”
Section: Introductionmentioning
confidence: 98%
“…Under such idealized conditions, we can extract the LCS for the true state and use this as our template for the directed launch of drifters. The approach we will adopt will, therefore, build on the ideas used by Poje et al (2002), and Toner and Poje (2004) to study how initial drifter placements influences the performance of our LaDA method. By targeting the Lagrangian flow structures of the 'true' system, we are able to simplify the problem drastically.…”
Section: Introductionmentioning
confidence: 99%